2023
DOI: 10.1177/15910199231162878
|View full text |Cite
|
Sign up to set email alerts
|

Determining flow stasis zones in the intracranial aneurysms and the relation between these zones and aneurysms’ aspect ratios after flow diversions

Abstract: Background Flow diverter stents (FDSs) are widely used to treat aneurysms in the clinic. However, even the same flow diverter (FD) use on different patients’ aneurysm sites can cause unexpected hemodynamics at the aneurysm region yielding low success rates for the overall treatment. Therefore, the present study aims to unfold why FDs do not work as they are supposed to for some patients and propose empirical correlation along with a contingency table analysis to estimate the flow stasis zones in the aneurysm s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similarly, a numerical study of six patient aneurysm geometries showed that aspect ratio impacted flow stasis after treatment (Altındağ et al. 2023). However, in another study of 21 patients treated with FDS, no geometric parameters (aneurysm size or volume and neck size) were found to influence treatment outcomes (Pereira et al.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, a numerical study of six patient aneurysm geometries showed that aspect ratio impacted flow stasis after treatment (Altındağ et al. 2023). However, in another study of 21 patients treated with FDS, no geometric parameters (aneurysm size or volume and neck size) were found to influence treatment outcomes (Pereira et al.…”
Section: Introductionmentioning
confidence: 94%